Portugal - Estanqueiro, Ana (2013)
In the past decades, Portugal has had little development of wind power plant installations, mainly due to the low tariffs practised. However, at the end of 2001, the scenario changed with the publication of new legislation and tariffs. By 2003, that change became reflected in the implementation of new wind park projects and a strong increase in the development rate of capacity installed. In the following sections, a synthesis of the past as well as a summary of the current situation is presented with a main focus on the Portuguese current state of development and trends.